Adventure time with Fionna & Cake : party bash blues - Sheridan, Kate (Kaboom!, 2019)
For Fionna's birthday, Prince Gumball and Marshall Lee throw a surprise party that gets out of hand when an experimental serum turns the birthday cake into a monster.